Dialogue of farming knowledge in the SENA at the Guainia - Gonzalez Torres, Fernando
The establishment of communicational lines to achieve an effective interchange of knowledge is the fundamental basis for successful pedagogical practices in intercultural contexts; contexts where the distinguished education must be adopted and recognised as a connector of cultures, with the purpose of achieving the recognition of relations between human beings in space and time. In the altruistic quest of rights inhabitants of a community must have to deploy their own ways of living; this article outlines these elements in the reconstruction of an investigative experience where a know-how dialogue has been developed with communities at the Ecotourism Environmental Centre in the Amazonian Northwest which contributed introducing conceptual elements for the processes of wild yucca farming.